BACTERIAL AND VIRAL INFECTIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bacterial and viral infections are a serious threat to the global health system. This article compares the etiological factors, pathogenesis and clinical manifestations of bacterial and viral infections. Bacteria are often sensitive to antibiotics and have a unique cell structure. Viruses are increased within the cell and live depending on the host cells. Differences in immune response, diseases and treatment are analyzed in detail. In addition, the effectiveness of antibiotics and antibal drugs will be covered by the efficiency and averture strategies. This article can effectively improve and treat inficated diseases in medical practice.